Regional Financial Performance and Inclusive Economic Development: Empirical Evidence From Provinces in Indonesia (Jurnal Bina Praja, 2023)
This study aims to analyze the relationship between regional financial performance and inclusive economic development in Indonesia using secondary data from 34 provinces in Indonesia from 2011-2021. The data sources for this study were collected from the National Development Planning Agency, Directorate General of Fiscal Balance, and Statistics Indonesia. This study uses panel data regression analysis with a fixed effect model because it can reduce bias compared to other panel data models, especially those caused by unobservable time-invariant variables. The results showed that regional financial performance, as measured by the fiscal decentralization ratio, fiscal independence ratio, capital expenditure ratio, and social assistance expenditure ratio, significantly influenced inclusive economic development in Indonesia. Fiscal decentralization and social assistance spending have a positive relationship with inclusive economic development. Meanwhile, fiscal independence and capital expenditure have a negative relationship with inclusive economic growth.
Keywords: regional financial performance; inclusive economic development; Indonesia